EDUKASI MANAJEMEN RISIKO SEBAGAI PENGEMBANGAN KOPERASI DI KABUPATEN BATANG - Mahirun Mahirun (LPPM Universitas Pekalongan, 2020)
The cooperative law has emphasized that cooperatives need to develop themselves more and be built to be strong and independent based on cooperative principles so that they can play a role as pillars of the national economy. Prioritizing the principle of kinship on the basis of social and economic principles needs attention by the cooperative manager. In line with this, good risk management can be carried out to minimize losses that may occur from the business being run. Based on this the Batang Regency Industry, Trade, Cooperatives and SMEs Office carries out the Bintek Development, Supervision and Recognition of Cooperative Achievement activities to be able to improve the performance of cooperatives in Batang Regency. The participants of the activity are the management of cooperatives and offices related to the method of presentation and discussion of questions and answers. The results of the activity show that the enthusiasm of cooperative managers in participating in these activities is very high, in theory they already know the importance of risk management so that the problem that arises is the implementation at the policy level of each cooperative.Keywords: Risk Management, Coaching, Supervision, Performance, Cooperatives